2003
DOI: 10.1029/2002jd003221
|View full text |Cite
|
Sign up to set email alerts
|

The quasi 2‐day wave observed in the polar mesosphere: Comparison of the characteristics observed at Tromsø and Poker Flat

Abstract: [1] A comparison of the quasi 2-day wave (Q2DW) observed at Tromsø (69.6°N, 19.2°E) and Poker Flat (65.2°, 147.6°W) is presented at four heights of 70, 76, 82, and 88 km using wind data taken for $4 years, from 1 November 1998 to 7 November 2002. The characteristics of the Q2DW such as seasonal variation, occurrence of period of maximum amplitude, ratio of meridional to zonal amplitudes, shape of altitude profile of phase, and modulation of amplitude at a 4-10 days rate found at Poker Flat are very similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
2
20
1
Order By: Relevance
“…This wave is believed to be one of a series of waves generated by barotropic instabilities in the polar night jet (e.g., Venne and Stanford, 1982; Hartmann, 1983;Prata, 1984;Lait andStanford, 1988 andManney et al, 1988). Nozawa et al (2003b) suggested that the polar MLT-region wintertime two-day wave may be an E2 wave connected to these stratospheric oscillations -but this could not confirmed in the absence of longitudinal measurements. Palo et al (2007) reported an E2 wave in the mid-latitude, summer, southern-hemisphere MLT region occurring simultaneously with a W3 wave.…”
Section: Introductionmentioning
confidence: 97%
“…This wave is believed to be one of a series of waves generated by barotropic instabilities in the polar night jet (e.g., Venne and Stanford, 1982; Hartmann, 1983;Prata, 1984;Lait andStanford, 1988 andManney et al, 1988). Nozawa et al (2003b) suggested that the polar MLT-region wintertime two-day wave may be an E2 wave connected to these stratospheric oscillations -but this could not confirmed in the absence of longitudinal measurements. Palo et al (2007) reported an E2 wave in the mid-latitude, summer, southern-hemisphere MLT region occurring simultaneously with a W3 wave.…”
Section: Introductionmentioning
confidence: 97%
“…In this study we concentrate on the investigation of the Q2DW. At mid-latitudes, the Q2DW is most pronounced in the summer mesosphere and only at high latitudes has the Q2DW been observed near winter solstice (Nozawa et al, 2003;Sandford et al, 2008;Tunbridge and Mitchell, 2009).…”
Section: Signatures Of the Quasi-2-day Wavementioning
confidence: 99%
“…Recent studies discussed a strong Q2DW activity around winter solstice at high latitudes (Nozawa et al, 2003;Sandford et al, 2008;Tunbridge and Mitchell, 2009) related to an eastward-propagating E2 wave using wind measurements from meteor radars and geopotential height from Aura MLS.…”
Section: Introductionmentioning
confidence: 99%
“…In January of that same year, Lieberman [1999] observed the two-day wave as a mesospheric disturbance packet containing W2 component with a period of about 3.5 days, as well as W3 and W4 components mentioned above. Nozawa et al [2003] suggested the predominace of W2 and W4 components over W3 in the higher northern latitudes between 76-88 km altitude. Recently, Wu et al [2008] noted a strong W2 component of the two-day wave signature in the equatorial upper mesosphere during January 2006 with a period slightly shorter than 2 days.…”
Section: Introductionmentioning
confidence: 99%